Facing a Property Lawsuit Experience (Comparative & International Education Series, 2022)
It has never occurred to me that I would need to deal with a courthouse in my life. As an international student at Texas A&M University, USA, avoiding issues with courts is a “must” to ensure the achievement of my graduation timeline. Nevertheless, we can never predict what is going to happen to us as humans. Thankfully, there is always “a good Samaritan” in every complex story. My personal experience with being supported in difficult times came from a stranger that I have never met in my life and in an unexpected time.